Global exponential stability of a class of neural networks with unbounded delays - Duong, Anh Tuan; Tran, Thi Loan (Ukrains’kyi Matematychnyi Zhurnal, 2008)
In this paper, the global exponential stability of a class of neural networks is investigated. The neural networks contain variable and unbounded delays. By constructing a suitable Lyapunov function and using the technique of matrix analysis, we obtain some new sufficient conditions for global exponential stability.